How does organizational leadership contribute to the firm performance through social responsibility strategies?. Issue 7 (July 2021) - Saeidi, Parvaneh; Robles, Lorenzo Adalid Armijos; Saeidi, Sayedeh Parastoo; Zamora, María Isabel Vera
Abstract: Despite the wide-ranging studies on Corporate Social Responsibility (CSR), firm performance, and Organizational Leadership (OL), there have been only a few studies examining the inter-relationship between them. Accordingly, this investigation has tried to investigate how OL contributes to the firm's performance through the CSR strategies. It has an internal orientation to CSR motivations compared to the existing studies that mostly considered the external factors in implementing of CSR in firms; also, it has a comprehensive view toward the firm's performance by considering both financial and non-financial aspects of performance. It could be said that this study has tried to answer the question of whether or not CSR can be as a mediator between the OL and firm performance. Data collection was performed from 285 manufacturing and consumer products firms located in Malaysia during the four-month period of June–September of 2020. AMOS Structural Equation Modeling (AMOS-SEM) method was applied to analyze the model. Following the Baron and Kenny approach in testing the hypotheses, it was found that the relationships of OL and financial performance, as well as OL and non-financial performance were partially mediated by CSR. In addition, the non-financial performance was found as a full mediator between the OL and financial performance. Further, the results revealed two full mediated relationships in this way that non-financial performance was a full mediator variable between CSR and financial performance, as well as CSR and non-financial performance which were found as two multiple full mediators between OL and financial performance. The results help Malaysian managers to understand their current status, capabilities, strong points and weaknesses in leadership regarding to CSR. Moreover, due to the positive effects of CSR on both firm's financial and non-financial performance, CSR is recommended to be integrated in leadership style and the organizational strategies in order to having better performance. Abstract : Organizational leadership; Corporate social responsibility; Financial performance; Non-financial performance; Malaysia.